Phoradendron bathyoryctum Eichler relieves acute nociceptive pain stimulus and carrageenan-induced inflammation in mice - Mariela Ortiz Rivas; Olga Heinichen; Wilfrido Arrua; Rosa Degen de Arrua; Derlis A. Ibarrola D.; Maria del Carmen Hellion-Ibarrola (Vitae)
Background: The genus Phoradendron belongs to the Santalaceae family and possesses several species with antitumor, cytotoxic, and immunomodulatory activity, where pain and inflammation are common symptoms. It is used in venereal and liver diseases in Paraguayan folk medicine. In addition, it claims to have tonic properties for the heart and central nervous system. Previous studies have shown that crude extract of Phoradendron bathyoryctum Eichler (Pb) has anxiolytic and antidepressant activity. Objective: This work aimed to determine the anti-nociceptive and anti-inflammatory activity ofPb using acute models in mice. Methods: the anti-nociceptive activity of Pb was evaluated using mechanical pressure (Randall-Selitto test), acetic acid (writhing test), and heat (hot plate test) noxious stimulus in mice. The anti-inflammatory activity was assessed through carrageenan-induced plantar edema in mice previously treated with Pb. Results: Presences of high polarity alkaloids, steroids/ free triterpenoids, leucoanthocyanidins, and tannins were detected in phytochemical studies. Oral doses of 30 (p<0.01) and 300 (p<0.001) mg/kg of Pb denoted a significant dose-dependent increase in pain threshold, using the Randall-Selitto and Writhing test (30; p<0.05; and 300; p<0.01. In addition, consistent with the above anti-nociceptive effect, an increase in the reaction latency time after oral administration of Pb at a dose of 300 mg/kg (p<0.05) in the hot plate test was denoted. Finally, a significant reduction of edema (30 mg/kg; p<0.01) induced by 1% carrageenan was evidenced, demonstrating a potential anti-inflammatory activity of Pb compared to the positive edema control. Interestingly, the anti-edematous activity of Pb showed a similar intensity response compared to the group treated with 10 mg/kg indomethacin (p<0.01). Conclusion: This work revealed that the crude extract of Pb can increase pain threshold, be compatible with an analgesic effect, and reduce edema (anti-inflammatory) induced by Carrageenan in mice. Further pharmacological and chemical studies are being conducted to elucidate molecular mechanisms and components involved in the observed effects.